2017
DOI: 10.1074/jbc.m116.747139
|View full text |Cite
|
Sign up to set email alerts
|

DHHC7 Palmitoylates Glucose Transporter 4 (Glut4) and Regulates Glut4 Membrane Translocation

Abstract: Insulin-dependent translocation of glucose transporter 4 (Glut4) to the plasma membrane plays a key role in the dynamic regulation of glucose homeostasis. We recently showed that this process is critically dependent on palmitoylation of Glut4 at Cys-223. To gain further insights into the regulation of Glut4 palmitoylation, we set out to identify the palmitoyl acyltransferase (PAT) involved. Here we report that among 23 mammalian DHHC proteins, DHHC7 is the major Glut4 PAT, based on evidence that ectopic expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 58 publications
1
61
0
1
Order By: Relevance
“…In contrast, we previously reported an at least 3-logunit reduction in virus infectivity in mutant viruses lacking UL20 or gK (2)(3)(4)(29)(30)(31)(32). We previously showed that GODZ and its most closely related paralog, SERZ-␤, have indistinguishable substrate specificities in vitro; in contrast, in vivo, the two enzymes have distinct distributions in the Golgi complex (19,49). While GODZ is highly restricted to the cis-Golgi network, SERZ-␤ is preferentially localized to the trans-Golgi network, and our previous results pointed to partial functional redundancy of GODZ and SERZ-␤ (19,49).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, we previously reported an at least 3-logunit reduction in virus infectivity in mutant viruses lacking UL20 or gK (2)(3)(4)(29)(30)(31)(32). We previously showed that GODZ and its most closely related paralog, SERZ-␤, have indistinguishable substrate specificities in vitro; in contrast, in vivo, the two enzymes have distinct distributions in the Golgi complex (19,49). While GODZ is highly restricted to the cis-Golgi network, SERZ-␤ is preferentially localized to the trans-Golgi network, and our previous results pointed to partial functional redundancy of GODZ and SERZ-␤ (19,49).…”
Section: Discussionmentioning
confidence: 94%
“…We previously showed that GODZ and its most closely related paralog, SERZ-␤, have indistinguishable substrate specificities in vitro; in contrast, in vivo, the two enzymes have distinct distributions in the Golgi complex (19,49). While GODZ is highly restricted to the cis-Golgi network, SERZ-␤ is preferentially localized to the trans-Golgi network, and our previous results pointed to partial functional redundancy of GODZ and SERZ-␤ (19,49). Thus, the smaller defects in virus replication seen in GODZ Ϫ/Ϫ cells than in experiments testing mutant viruses are likely due to compensation for loss of GODZ function by SERZ-␤.…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of DHHC proteins exists in eukaryotic cells, including 8 in yeast (11), (12) and 23 in humans (13). Various studies, including our own, indicate that DHHC proteins possess distinct but overlapping substrate specificities (14), (15), (16). As palmitoylation controls a variety of important cellular processes, it is not surprising that several DHHC proteins are implicated in human disease (17), (18), (19), (20), (21).…”
Section: Introductionmentioning
confidence: 95%
“…Palmitoyl transferases with this DHHC configuration are present in all eukaryotes and occur as multienzyme families that range in size from 5 to 24 members (16,17). They play multiple critical roles in physiology and a variety of diseases, including cancer, Huntington's disease, and X-linked intellectual disability (18)(19)(20)(21)(22). GODZ is highly conserved between humans, mice, rats, fruit flies, and Caenorhabditis elegans, with 97% homology between humans and mice (23).…”
mentioning
confidence: 99%